Monolithic integration of a 10 μm cut-off wavelength InAs/GaSb type-II superlattice diode on GaAs platform - D. C. M. Kwan; M. Kesaria; J. J. Jiménez; V. Srivastava; M. Delmas; B. L. Liang; F. M. Morales; D. L. Huffaker (Scientific Reports, 2022)
Abstract At room temperature, a 10 µm cut-off wavelength coincides with an infrared spectral window and the peak emission of blackbody objects. We report a 10 µm cut-off wavelength InAs/GaSb T2SL p-i-n diode on a GaAs substrate with an intentional interfacial misfit (IMF) array between the GaSb buffer layer and GaAs substrate. Transmission electron microscopy and energy-dispersive X-ray spectroscopy revealed that the heterostructure on GaSb-on-GaAs is epitaxial, single-crystalline but with a reduced material homogeneity, extended lattice defects and atomic segregation/intermixing in comparison to that on the GaSb substrate. Strain-induced degradation of the material quality is observed by temperature-dependent current–voltage measurements. The T2SL with the IMF array appears as a potentially effective route to mitigate the impact of the lattice mismatch once its fabrication is fully optimized for these systems, but additional strain compensating measures can enable a low cost, scalable manufacturing of focal plane arrays (FPA) for thermal imaging cameras for spectroscopy, dynamic scene projection, thermometry, and remote gas sensing.